Answer:
When adding these two equations we get the value of x is
and y is
![(52)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/73lfnoi6no7sau9wxowmtad6ip7i3nhldq.png)
Therefore
and and
![y=(52)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h63eq6wqgz1hxx8tv0so2ugz1ou93te12l.png)
Explanation:
Given two equations are
![5x-y=6\hfill (1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qjmsb5kd0xszbos3aeqnjqltrt7k2u8q9n.png)
To find the addition of these two given equations :
Adding the equations (1) and (2) we get
5x-y=6
-2x+y=8
_______
3x=14
![x=(14)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/25zt83gnrh9knrx9i6o1ragip6b38f8uvy.png)
Substitute the value
in equation (1) we get
![5((14)/(3))-y=6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/a7n9m5kailxctxf8u0tj0aoylra7fqfj81.png)
![-y=6-(70)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/m9mq6re8yeev3p960tph32zei4zyunsnd0.png)
![-y=(18-70)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/toa154vzs9dz2rshol60c7zywh6ciu0mjk.png)
![-y=-(52)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/57ashc6151eezniumes3dj7jf6r1hpolga.png)
Therefore
![y=(52)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h63eq6wqgz1hxx8tv0so2ugz1ou93te12l.png)
When adding these two equations we get the value of x is
![(14)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kj07s8coma4f8l0iu8nqkauvd9izt4ef1o.png)
Therefore
and
![y=(52)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h63eq6wqgz1hxx8tv0so2ugz1ou93te12l.png)